GPU simulation of wake effects at the Horns Rev 1 offshore wind farm using the CFD porous disk wake model. Issue 2 (April 2023) - Uchida, Takanori; Tanaka, Teppei; Shizui, Ryuta; Ichikawa, Hiroto; Takayama, Ryo; Yahagi, Kazuomi; Okubo, Ryoya
To verify the effectiveness of the GPU simulation of wake effects at a large-scale offshore wind farm, we ran an in-house large-eddy simulation (LES) solver with a CFD porous disk wake model for the Horns Rev 1 wind farm. For this numerical research, we prepared the latest workstation equipped with a Xeon W-2265 CPU and an NVIDIA RTX A6000 GPU. We clarified that the calculation speed of the single GPU of the NVIDIA RTX A6000 is approximately 10 times faster than the calculation speed of the Xeon W-2265. Careful data analysis and visualization of the unsteady turbulent flow fields obtained in the current LES study suggest that the mutual interference of the wakes developed by wind turbines may frequently form a local speed-up region around wind turbines, located on the downstream side of large offshore wind farms.